Predicting Switching intention Among Generation Z (Study on Shopee App) - Purnama Putri, Viajeng (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
Studies that focus on the interaction of variables related to system quality, information quality, and service quality, as well as their effect on user satisfaction and subsequent intentions to switch to alternative e-commerce platforms can provide a better understanding of Generation Z's Customer behavior in using e-commerce applications. The approach used in this study is a quantitative approach. This study is to test the variables that affect switching intention with analysis tools using PLS software. This pathway analysis technique will be used in testing the magnitude of the contribution indicated by the path coefficients on each path diagram of causal relationships between IQ, SQ, SyQ, SI variables, on ST. The population is 188,951 people with sample of this study was Gen Z totaling 125 respondents. The results showed that Information Quality does not affect Customer satisfaction and the switching intention at shopee, but system quality affect the satisfaction and switching intention. The service quality has no effect on switching intention but affects customer satisfaction. Customer satisfaction affects the desire to change applications. Customer satisfaction mediates the relationship between service quality, system quality and the switching intention from shopee. However, it does not mediate the relationship between Information Quality and the switching intention Keywords: Service Quality, Information Quality, System Quality, Switching Intention, Customer Satisfaction